2022
DOI: 10.1155/2022/3047425
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin-3,3 -Digallate Protects Cartilage from Degradation by Modulating Inflammation and Antioxidant Pathways

Abstract: Background. Osteoarthritis (OA) is a common degenerative joint disease that may be closely linked to inflammation and oxidative stress destroying the balance of cartilage matrix. Theaflavin-3,3 ′ -digallate (TFDG), a natural substance derived from black tea, has been reported to restrict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Eighteen male C57 mice (8 weeks old, weighing between 18 and 22 g) were purchased from the Experimental Animal Center of Nanchang University and housed in a dark/light cycle environment at 20–25°C, with open water and food access. To establish an animal OA model, Destabilized medial meniscus (DMM) (Lin et al., 2022; Teng et al., 2022) surgery took place under pentobarbital anesthesia. By taking the control group as the sham group, the joint capsule was incised without damaging the cartilage and meniscus, while the joint cavity was injected with PBS equal to GAA every week.…”
Section: Methodsmentioning
confidence: 99%
“…Eighteen male C57 mice (8 weeks old, weighing between 18 and 22 g) were purchased from the Experimental Animal Center of Nanchang University and housed in a dark/light cycle environment at 20–25°C, with open water and food access. To establish an animal OA model, Destabilized medial meniscus (DMM) (Lin et al., 2022; Teng et al., 2022) surgery took place under pentobarbital anesthesia. By taking the control group as the sham group, the joint capsule was incised without damaging the cartilage and meniscus, while the joint cavity was injected with PBS equal to GAA every week.…”
Section: Methodsmentioning
confidence: 99%
“…They have a 3-hydroxyflavone backbone, and they offer several benefits for various pathologies, particularly those with an inflammatory etiology. Two molecules, Epigallocatechin-3-O-gallate (EGCG) and Theaflavin-3,3’-Digallate (TFDG), have been studied in two manuscripts [ 41 , 42 ]. In Yang et al (2022a), it was found that EGCG could alleviate chondrocyte injury, as mimicked in vitro by treating the CHON-001 cell line with IL-1β, reducing MMP-13 and IL-6 expression and release.…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%
“…EGCG’s activities appear to be associated with decreased levels of the microRNA miR-29b-3p, which targets phosphatase and tensin homolog (PTEN) mRNA, and then increases its expression, as indicated by the reversal of EGCG activities by MiR-29b-3p mimic. Further confirmation was provided by PTEN overexpression, which showed that it could abrogate the effects of miR-29b-3p mimics in IL-1β-treated CHON-001 cells, highlighting the known nutrigenomic effect of EGCG [ 41 ]. TFDG, a natural compound found in black tea, was found to increase the proliferation of IL-1β-treated chondrocytes, as well as increase ECM deposition (ACAN and Col-II) and reduce ECM degradation (decrease in MMP-13, MMP-3, and ADAMTS5).…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%
“…Recent research has revealed that circ-ITCH (hsa_circ_0001141: circular RNA itchy E3 ubiquitin protein ligase) can modulate the nuclear factor erythroid-derived 2-related factor 2 (Nrf2) pathway to inhibit oxidative stress and improve diabetic complications . Although TFDG has been shown to regulate the Nrf2 pathway in some previous studies, , the effect of TFDG on circRNA has been less well studied. In the current research, we delve deeper into the function of circ-ITCH in diabetic liver and kidney injury and in the activation of the Nrf2 pathway regulated by TFDG.…”
Section: Introductionmentioning
confidence: 99%